Manajemen Esktrakurikuler KB Happy Bear Kota Magelang - Masyithoh, Syari’ati (ACIECE, 2019)
Extracurricular management is an organized management process in which there is planning, organizing, directing and supervising extracurricular activities carried out in a school institution. The formulation of this research is what extracurricular activities are in the Happy Bear KB in Magelang City and how is the extracurricular management process implemented in the Happy Bear KB in Magelang City. The study was conducted at KB Happy Bear Magelang City. The research method used is descriptive qualitative. Principals and teachers are sources of data in this study. Data collection techniques carried out by interview, observation, and documentation. Data analysis in this research was carried out through data reduction, data display, and conclusion drawing. The results of this study can be concluded that the management of extracurricular activities at KB Happy Magelang City is running well and the extracurricular activities that are held facilitate early childhood with special needs. As for some extracurricular activities in KB Happy Bear Magelang City namely painting and pencak silat which is held once a week